Values of waist/hip ratio among children and adolescents from bogotá, colombia: The fuprecol study (2015)
Objective: the aim was to establish reference standards for waist/hip ratio among Colombia children and adolescent aged 9 to 17.9 years who participated in “The FUPRECOL Study”. Methods: cross-sectional study. A sample of 3 005 children and 2 916 adolescents healthy Colombian youth (boys n = 2 542 and girls n = 3 384) participated in the study. Height, weight, waist circumference, hip circumference and sexual maturation status were measured. Reference curves were fitted with the LMS method (L [curve Box– Cox], M [curve median] and S [curve coefficient of variation]), for boys and girls, stratified by age group, and to compare them to international references. Results: in all ages, the waist/hip ratio was higher in boys than in girls. Subjects whose waist/hip ratio was above the 90th percentile of the standard normal distribution were considered to have high cardiovascular risk (boys range 0.87 to 0.93 and girls range 0.85 to 0.89). Overall, our waist/hip ratio values were lower than Europe, Asia and Africa values and similar to those of some Latin American references. Conclusions: values reference charts for waist/hip ratio values specific for age and sex, obtained from children and adolescents from Bogota, Colombia, are provided. They may be used regionally, both for nutritional assessment and to predict cardiovascular risks in early age. © 2015, Grupo Aula Medica S.A. All rights reserved.